Facile and improved synthesis of the 2-O-β-d-glucopyranosyl-l-ascorbic acid. (31st January 2023) - He, Lili; Ji, Jingwen; Sun, Jian; Pengjuan, Zhou; Zhai, Lijuan; Tang, Dong; Mu, Yangxiu; Wang, Ling; Yang, Haikang; Ji, Jinbo; Iqbal, Zafar; Yang, Zhixiang
Graphical abstract: Abstract: 2- O -β-d -glucopyranosyl-l -ascorbic acid (AA-2βG ) provides a source of sustained release of ascorbic acid (vitamin C) upon α-glucosidase activity inside the human body, and is therefore an ingredient of cosmetics, food, and medicinal products. Commercial synthesis of the compound is highly demanded and is attempted from time to time, aimed at improved and commercially viable strategies. We synthesized the AA-2βG in five steps starting from ascorbic acid with a 31.4% overall yield. The synthetic steps do not need column purification except one, and the final product is pure enough to be utilized for application purposes.